1973
DOI: 10.1038/bjc.1973.36
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Clonogenic Growth of Tumour Cells and Metastases in the Lungs by Local X-Radiation

Abstract: Single cell suspensions of two allogeneic tumours (W-256 and Y-P388) injected intravenously produced macrocolonies in the lungs of rats. Colony forming efficiency (CFE, the number of colonies produced by each viable cell injected) was low in 6-week or older rats but was markedly increased by 1000-1500 rad local thoracic irradiation (LTI) given 7-14 days before the tumour cell injection, or by antilymphocytic serum (ALS) but not by sublethal whole body irradiation (WBI). Similarly, LTI increased the incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1974
1974
1998
1998

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 5 publications
3
22
0
Order By: Relevance
“…The suggestion is that a first preoperative radiation dose should not be too low. It has been suggested that the anterior surface of the lung would have received more than 22 rad of scattered radiation measured at the centre of the body, and this may lead to the trapping of extra metastases den (Van Brenk et al, 1973). However, this explanation is unlikely because, in another experiment, Sheldon (1974) showed, with tumours also transplanted on the anterior chest wall, that the number of metastases in each lobe of the lungs were simply proportional to the size of each lobe, for both irradiated and control mice.…”
Section: Local Controlmentioning
confidence: 99%
“…The suggestion is that a first preoperative radiation dose should not be too low. It has been suggested that the anterior surface of the lung would have received more than 22 rad of scattered radiation measured at the centre of the body, and this may lead to the trapping of extra metastases den (Van Brenk et al, 1973). However, this explanation is unlikely because, in another experiment, Sheldon (1974) showed, with tumours also transplanted on the anterior chest wall, that the number of metastases in each lobe of the lungs were simply proportional to the size of each lobe, for both irradiated and control mice.…”
Section: Local Controlmentioning
confidence: 99%
“…injection with a single-cell suspension of tumour cells (Withers and Milas, 1973;van den Brenk et al, 1973a;Thompson, 1974). One of us (Janik, 1976) has recently confirmed this effect, using the tumour employed in the present experiments.…”
supporting
confidence: 53%
“…THE PROPORTION of intravenously injected allogeneic tumour cells which survived and formed macrocolonies in the lungs of rats (colony forming efficiency, CFE) is relatively small (less than 1%), but CFE was greatly increased if the lungs of recipients had been treated locally with x-ravs before the tumour cells were injected (van den Brenk, Sharpington and Orton, 1973a;van den Brenk et al, 1973b). In mice, local x-irradiation of the lungs also stimulated CFE of intravenously injected syngeneic tumour cells (Withers and Milas, 1973).…”
mentioning
confidence: 99%